CPC-136 The Effects of Using a Treatment Plan For Dispensing Biological Drugs in Rheumatic Diseases in ASP 8 of Syracuse, Italy. (12th March 2013) - Ferlito, F; Spadaro, D; Sgarlata, D; Sorbello, R; Guzzardi, S; Migliorisi, E; Avola, N; Regolo, S; Cacciaguerra, G
Abstract : Background: Rheumatic diseases are chronic diseases with a high cost. New drugs are the anti-TNF inhibitors adalimumab (A) and etanercept (E). The Infectious Diseases Unit of Umberto I Hospital, Syracuse, Italy, was identified as a Regional Centre for the prescription of biologicals. Furthermore, D.A. 0264/16.02.2011 authorised a regional Treatment Plan (PT) by which these drugs are to be dispensed, health care costs and appropriateness of prescription monitored. Purpose: To evaluate the consequences of the PT and the effects of A and E on PCR values and number of joints involved (NJI). Materials and Methods: The PT is annual and consists of two sections containing: 1. Demographic features, diagnosis, prior therapy with any failures, clinical and laboratory data (NJI, PCR), date of first prescription and dose of biological agent. 2. Follow-up at 6 months, with the assessment of therapeutic efficacy (excellent, good, adequate, inadequate), side effects and updated clinical data. Results: Overall, 56 PTs were examined: 32.7% of patients (mean±SD age: 50.7 ± 12.1) taking A and 67.3% (mean±SD age: 54.1 ± 13.7) taking E. In subjects treated with A the PCR values were: 0.5 ± 1.0 g/dl (baseline) and 0.1 ± 0.2 g/dl (6 months); NJI were: 11.9 ± 7.2 (baseline) and 10.1 ± 9.2 (6 months). In subjects treated with E, the PCR values were: 2.5 ± 6.2 g/dl (baseline) and 1.2 ± 3.9 g/dl (6 months); NJI were: 15.4 ± 10.8 (baseline) and 8.2 ± 8.2 (6 months). Conclusions: The use of A and E has been shown to improve the clinical condition of the patients. Furthermore, the use of the PT has allowed all patients with rheumatic diseases in the province of Syracuse to access a dedicated health facility, reducing their physical/economic inconvenience. A significant economic benefit was recorded for the ASP 8, not having to refund the costs of flow-compensation activation (File F). No conflict of interest.